Chapter A fragmentary story: episcopal culture in Milan during Lothar I's reign? - Tessera, Miriam Rita (Reti Medievali E-Book, 2022)
Dealing with episcopal culture in Milan during Lothar I's age (822-855), that is the age of Archbishop Angilbert II (824-859), is a difficult task, because of the lack of sources and uncertain origin of many extant manuscripts. As a matter of fact, Angilbert II shared a common cultural background with his transalpine colleagues, but he had to face the loss of the schools in Milan and to rebuild a cultural system which could also improve the political role of his see to the detriment of Pavia. This paper analyses some main features of his cultural policy: the activity of masters accustomed to the new ideas of Carolingian schools, in particular the role played by Hildemar and his library in Civate; the renewal of St. Ambrose's cult and Angilbert's iconographical choices on the golden altar of Sant'Ambrogio, in connection with literary activity in Milan (as for the case of bishop Mansuetus' letter copied in Montpellier, Bibliothèque Interuniversitaire, Faculté de medicine, H 233).